The Trichoptera of Panama XXVIII. Nine new species of microcaddisflies (Trichoptera, Hydroptilidae) - Brian J. Armitage; Steven C. Harris; Viterbo Rodriguez (Neotropical Biology and Conservation)
In this study, we describe and illustrate nine new species of microcaddisflies: Oxyethira jaramillo sp. nov., Neotrichia afuera sp. nov., Neotrichia aguirrei sp. nov., Neotrichia betegui sp. nov., Neotrichia rancheria sp. nov., Neotrichia sona sp. nov., Metrichia riosi sp. nov., Ochrotrichia mariettae sp. nov. and Ochrotrichia martinez sp. nov. The majority of these new species were collected on the Soná Peninsula or offshore on the Coiba National Park islands. With these additions, there are now 544 species of caddisflies known from Panama, distributed amongst 15 families and 56 genera.